IRESCUE – Interventional embolization of Renal artEries after SurgiCal or traUmatic injury with hEmorrhage. Issue 136 (March 2021) - Öcal, Osman; Puhr-Westerheide, Daniel; Mühlmann, Marc; Deniz, Sinan; Fabritius, Matthias Philipp; Weinhold, Philipp; Wildgruber, Moritz; Ricke, Jens; Seidensticker, Max
Highlights: Interventional embolization is safe and effective in renal bleeding cases. Acute kidney injury is not infrequent, but self-limiting and without long-term deterioration in kidney functions. Compared to surgical treatment, endovascular approach should be preferred due to minimally invasive nature of the procedure. Abstract: Objectives: To evaluate the efficacy and safety of urgent percutaneous embolization for the treatment of acute renal hemorrhage. Materials and Methods: All patients undergoing endovascular embolization at our hospital for bleeding from renal artery branches between January 2010 and June 2020 were retrospectively evaluated. Periprocedural characteristics, technical details, clinical outcomes, and complications were documented. Results: Seventy-six patients with a mean age of 67.3 ± 12.9 underwent 86 procedures. The most common cause of hemorrhage was iatrogenic (63/76), including 44 patients presenting after partial nephrectomy. Bleeding was successfully controlled in 80 of 86 procedures (92.8 % technical success), and clinical success (defined as control of bleeding with endovascular embolization) was achieved in 72 of 76 patients (94.5 %) with embolization, including seven patients undergoing re-intervention. In univariate analysis, risk factors for clinical failure were antiplatelet agents (p = 0.033), and technical failure (p < 0.001); and technical failure was the only significant risk factor in multivariate analysis. Only one patient (1.3 %) needed nephrectomy. AKI was seen after 16 (21 %) procedures, and preprocedural increased creatinine (≧1.8) and decreased GFR (<60) were risk factors for AKI (p = 0.022 and p = 0.020). In all patients except one, renal functions returned to baseline. One patient died because of pulmonary embolism (in-hospital mortality 1.3 %). Conclusion: Interventional embolization is feasible, safe, and effective in the treatment of renal hemorrhages. Among others, the complication management with minimally invasive procedures allows urologists to safely perform partial nephrectomy even in patients with central, large, and endophytic tumors, thereby preserving kidney function in these patients.